2022
DOI: 10.3390/en15030702
|View full text |Cite
|
Sign up to set email alerts
|

A New Graphitic Nitride and Reduced Graphene Oxide-Based Sulfur Cathode for High-Capacity Lithium-Sulfur Cells

Abstract: Lithium-sulfur (Li-S) batteries can provide at least three times higher energy density than lithium-ion (Li-Ion) batteries. However, Li-S batteries suffer from a phenomenon called the polysulfide shuttle (PSS) that prevents the commercialization of these batteries. The PSS has several undesirable effects, such as depletion of active materials from the cathode, deleterious reactions between the lithium anode and electrolyte soluble lithium polysulfides, resulting in unfavorable coulombic efficiency, and poor cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(92 reference statements)
1
1
0
Order By: Relevance
“…The 2θ and intensity data of the XRD measurement were processed on an XRD diffractogram using Origin-2018 software. The XRD analysis results (Figure 2) showed that the peaks generated at 2θ = 15.5°, 23.1°, 25.9°, 27.8°, 28.7°, 34.2°, 42.7°, 51.3°, among others, on the XRD diffractogram of the asprepared sulfur correspond with the diffraction pattern (Joint Committee on Powder Diffraction Standards, JCPDS No-34-0941) for standard monoclinic phase sulfur and are consistent with the ICDD PDF card number 00-008-0247 (Suzanowicz et al, 2022). Based on the calculation using the XRD software (Integrated Xray powder diffraction software: Rigaku PDXL2), the crystallite size was 37 nm and the crystallinity was 63%.…”
Section: Resultssupporting
confidence: 78%
“…The 2θ and intensity data of the XRD measurement were processed on an XRD diffractogram using Origin-2018 software. The XRD analysis results (Figure 2) showed that the peaks generated at 2θ = 15.5°, 23.1°, 25.9°, 27.8°, 28.7°, 34.2°, 42.7°, 51.3°, among others, on the XRD diffractogram of the asprepared sulfur correspond with the diffraction pattern (Joint Committee on Powder Diffraction Standards, JCPDS No-34-0941) for standard monoclinic phase sulfur and are consistent with the ICDD PDF card number 00-008-0247 (Suzanowicz et al, 2022). Based on the calculation using the XRD software (Integrated Xray powder diffraction software: Rigaku PDXL2), the crystallite size was 37 nm and the crystallinity was 63%.…”
Section: Resultssupporting
confidence: 78%
“…Many efforts have been made to solve the problems of Li-S batteries. From the aspect of the sulfur cathode, a common approach is designing a catalytic carbon material to load sulfur so that it encapsulates and traps lithium polysulfide before it dissolves in the electrolyte [6,7] . However, the structural design of cathode materials is complicated, the cost is high, the yield is low, and this method is difficult to apply on a large scale [8,9] .…”
Section: Introductionmentioning
confidence: 99%